(untitled) (AYUSHDHARA, 2025)
Mental health disorders, known as Manas Rogas in Ayurveda, are a growing global health concern. Ayurveda provides a holistic approach to mental well-being, encompassing both Dravyabhuta chikitsa (pharmacotherapy) and Adravyabhuta chikitsa (non-pharmacological interventions). This case report explores the potential role of Viddhakarma (specifically Siravedha), described by Acharya Sushruta, as a component of Trasana Chikitsa in the management of Manas Rogas, with a focus on GAD, considering the association of Vata vitiation with anxiety. Materials & Methods: A 32-year-old male patient, diagnosed with moderate to severe GAD (Hamilton Anxiety Rating Scale [HAM-A] score of 28), underwent Viddhakarma (Trasana chikitsa) in conjunction with conventional Ayurvedic medications as part of a comprehensive treatment plan. Symptoms severity was assessed using the HAM-A, and subjective improvements in sleep quality and emotional well-being were documented. Results: The patient demonstrated a significant reduction in anxiety symptoms, with the HAM-A score decreasing to 8. Subjective improvements in sleep quality and a reported sense of calmness and emotional well-being were also observed following the combined Viddhakarma and Ayurvedic intervention. Discussion: This case suggests that Viddhakarma, when integrated within a comprehensive Ayurvedic treatment protocol, may offer potential benefits in the management of GAD. The purported mechanism of Viddhakarma, involving Vata regulation and Dosha elimination through bloodletting, warrants further investigation.